Senile asthenia: clinical aspects of the perioperative period and anesthesia - R. R. Gubaydullin; E. V. Mikhaylov; V. V. Kulakov (Вестник анестезиологии и реаниматологии, 2020)
The objective: to summarize data from publications devoted to the problems faced by clinicians when managing patients with senile asthenia.Results: the growing number of surgical patients of elderly and senile ages aggravates the negative statistics of complications and treatment results, thus it is necessary to search for a comprehensive effective solution to this problem. Understanding the pathophysiological models causing senile asthenia allows not only focusing on early diagnosis and management of potential complications but also preventing their development. Risk stratification, comprehensive diagnosis of functional status and geriatric syndromes in the light of a possible adverse postoperative period make it possible to choose the optimal analgesia and perioperative management of a patient with senile asthenia. The clinical organization of the treatment process and rehabilitation treatment based on multidisciplinary interaction in such patients improves postoperative results.